APPLICATION OF GENOMIC AND GENETIC ENGINEERING TOOLS FOR IMPROVEMENT OF GRAPEVINES - A. Mwamahonje; 1 Z. Maseta; 1 F. Mlalila; T. Feyissa (Journal of Animal and Plant Sciences, 2020)
Conventional breeding in grape is tedious and time-consuming. The long juvenile phase of grape delays first flowering and fruit setting. Use of genomic tools including, genetic engineering, functional genomics, genome wide association and bioinformatics facilitate exploitation of traits to shorten breeding cycles. Short breeding cycles can be achieved by selection and screening of the best cultivars in the genebank. However, it is time consuming to develop new cultivars. The incorporation of traits to the new grape cultivar is done through conventional breeding by crossing male and female parents with contrasting traits. In addition, application of molecular markers can easily identify Quantitative Trait Loci (QTLs) influencing traits of interest for fastening introgression into the recipient grape cultivars by backcrossing method. Genetic engineering is another tool that uses Agrobacterium tumefaciens and biolistic mediated transformation whereby targeted genes are inserted into a DNA of a new grape cultivar for regeneration for example, grape transgenes. In a hybridization study, in which a seedless cultivar is used as maternal genotype, embryo rescue technique is necessary. Some traits in consideration in grape breeding include, flowering time, yield, drought tolerant, diseases resistance, sugar content and wine quality. Therefore, the application of genomic and genetic engineering tools is inevitable for grape improvement.
Keywords: Biotechnology; Breeding; Germplasm; Molecular Marker; QTL; Trait